In Situ Electron Paramagnetic Resonance Investigation of Isotope-Selective Breathing in MIL-53 During Dihydrogen Adsorption - Fernadi Lukman, Muhammad; Chetry, Sibo; Sarkar, Prantik; Bon, Volodymyr; Thangavel, Kavipriya; Kaskel, Stefan; Hirscher, Michael; Krautscheid, Harald; Pöppl, Andreas (Chemistry - A European Journal, 2025)
The development of smart materials capable of separating dihydrogen isotopologues has risen recently. Among potential candidates, the flexible MIL-53 (Al) has been gaining attention due to its structural flexibility providing the so-called ‘’breathing mechanism’’ that can be useful to separate hydrogen isotopologues selectively. In the present work, an in situ continuous wave electron paramagnetic resonance investigation has been proven as a sensitive technique to follow the isotopologue-selective adsorption-desorption of dihydrogen species on the paramagnetic metal-doped MIL-53 (Al0.99Cr0.01) and MIL-53 (Al0.99V0.01), respectively. The presence of paramagnetic spin probes such as Cr3+ and V4+ inside the MIL-53 framework allows for monitoring the framework transition including the 2nd transition step that selectively occurs at p>100 mbar when D2 gas is adsorbed on the pores at 23 K. Furthermore, investigation of D2 desorption from MIL-53 (Al0.99V0.01) by temperature-dependent hyperfine spectroscopy provides a more detailed analysis of the D2 desorption process on a microscopic scale with respect to the embedded spin probe.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Breathing; dihydrogen; EPR; in situ; MIL-53